2014
DOI: 10.1590/brag.2014.020
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance and stability of andean common bean lines with white grains in Brazil

Abstract: This work evaluated the effect of genotype by environment interaction in Andean common bean lines with white grains, in Central Southern Brazil, to identify lines with high agronomic performance, stability and adaptability, aiming to meet domestic demand and to increase the Brazilian participation in the foreign market of common bean. Nineteen trials with twelve Andean lines were conducted in , 2008 Grain yield and other agronomic traits were evaluated. Data were subjected to analysis of variance and of adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…A significant C x E interaction has previously been described for flowering (Mambrin et al, 2015), cycle Ribeiro et al, 2004Ribeiro et al, , 2014, insertion of the first pod (Ribeiro et al, 2014;Maziero et al, 2015), and grain yield (Elias et al, 2007;Melo et al, 2007;Rocha et al, 2010;Pontes Júnior et al, 2012;Domingues et al, 2013;Silva et al, 2013;Pereira et al, 2009aPereira et al, ,b, 2010Pereira et al, , 2014Barili et al, 2015a,b) in experiments evaluating the performance of common bean cultivars. The existence of a significant C x E interaction indicates that the stability analyses may be useful for the identification of superior cultivars.…”
Section: Joint Analysis Of Variancementioning
confidence: 83%
See 1 more Smart Citation
“…A significant C x E interaction has previously been described for flowering (Mambrin et al, 2015), cycle Ribeiro et al, 2004Ribeiro et al, , 2014, insertion of the first pod (Ribeiro et al, 2014;Maziero et al, 2015), and grain yield (Elias et al, 2007;Melo et al, 2007;Rocha et al, 2010;Pontes Júnior et al, 2012;Domingues et al, 2013;Silva et al, 2013;Pereira et al, 2009aPereira et al, ,b, 2010Pereira et al, , 2014Barili et al, 2015a,b) in experiments evaluating the performance of common bean cultivars. The existence of a significant C x E interaction indicates that the stability analyses may be useful for the identification of superior cultivars.…”
Section: Joint Analysis Of Variancementioning
confidence: 83%
“…The Diamante Negro cultivar was stable for grain yield on both biplots; however, it was ranked sixth for grain yield (Table 3). Similarly, Domingues et al (2013) and Pereira et al (2014) observed that not all stable lines, identified by the AMMI method, were those with higher grain yields.…”
Section: Stability For Insertion Of the First Pod And Grain Yieldmentioning
confidence: 92%
“…In recent years, the quantification of GEI and yield stability studies involving several cereal crops have been done (Benin et al, 2012;Forkman & Piepho, 2014;Pereira et al, 2014;Carvalho et al, 2016). Current assay evaluates the genotypic stability and adaptability of nine maize genotypes in seven environments using AMMI and GGE models.…”
Section: Introductionmentioning
confidence: 99%
“…Significant interaction effects were found between varieties and sowing date on number of days to flowering of green bean (Seyum, 2014; Hussein and Abd El-Hady, 2015 on cowpea). Significant interaction effects was found between varieties and sowing date on fibers content trait of green bean ( Pereira et al (2014) found that the genotype × environment interaction differed significantly for tolerant rust disease trait.…”
Section: Introductionmentioning
confidence: 95%